Civil Liability of Marketplaces for Consumer Losses Due to Fraud by Third-Party Sellers - Kurniawan, Deni; Prasetyawati, S Endang (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The advancement of information technology has driven the emergence of marketplace platforms as key facilitators of electronic transactions. However, the increasing number of fraud cases by third-party sellers raises legal issues concerning who bears responsibility for consumer losses. This study aims to analyze the civil liability of marketplaces for consumer losses caused by third-party fraud within the framework of civil law and consumer protection. This research employs a normative juridical method through statute and case study approaches. The findings reveal that marketplaces can be held liable if they prove negligent in their seller verification systems, monitoring mechanisms, or fail to provide an effective dispute resolution process. Consequently, the application of strict liability principles should be considered to strengthen legal protection for consumers in digital transactions.